mseffs
contestada

Place the following steps in order to complete the square and solve the quadratic equation,
x2 - 6x + 7 = 0.
x2 - 6x + 9 = -7+9
x = 3 + 2
V(x - 3)2 = v2
(x - 3)2 = 2
(x - 3) = tv2
x2 - 6x = -7

Respuesta :

frika

Answer:

See explanation

Step-by-step explanation:

Given the equation

[tex]x^2-6x+7=0[/tex]

Step 1: Add -7:

[tex]x^2-6x=-7[/tex]

Step 2: Add 9:

[tex]x^2-6x+9=-7+9\\ \\x^2-6x+9=2[/tex]

Step 3: Use perfect square formula:

[tex]x^2-6x+9=(x-3)^2\\ \\(x-3)^2=2[/tex]

Step 4: Take square root:

[tex]\sqrt{(x-3)^2}= \sqrt{2}[/tex]

Step 5: Simplify:

[tex]x-3=\sqrt {2}\text{ or }x-3=-\sqrt{2}[/tex]

Step 6: Add 3:

[tex]x=3+\sqrt{2}\text{ or }x=3-\sqrt{2}[/tex]